Beyond the Inclusive Possibility: Understanding Human Trafficking in the Unexplored Directions. An Explorative Assessment in the Indian Context - Kumar, Surender; Saini, Manish Kumar; Sarmah, Papori (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Objectives: To study human trafficking and its typology, and various socio-cultural, political, economical triggers responsible for this sinister social reality, and also analyze gender and age-based victimization’ also simultaneously examine the international and domestic laws to combat human trafficking and its implementable capacities. Subjects and methods: The proposed examination was an exploratory, qualitative sample-based survey study. The body of data analyzed was mustered up from multiple sources, primarily from the students of University level enrolled in various studies, including social workers, community activists through convenient and judgmental sampling spread over 6 months, and the contents were analyzed. Results: Various socio-cultural, political, and economic grounds were observed for human trafficking for its various heinous purposes. Gender-based victimization and age-based victimization in the version of child trafficking were the prominent findings. The loopholes and shortcomings in various laws to shackle human trafficking were discovered. It was also further examined that most of the laws and socio-cultural ambiance are not victim-friendly and do not stop secondary victimization of the trafficked victims. Conclusion: Human trafficking has wide-ranging socio-cultural, economical, environmental, and political triggers in India; which have continued for a huge span of time in many parts and locations of the country. The nature of most of the problems resembles that in many other parts of the world. The present status and higher vulnerability of women and children in the domain of human trafficking for various purposes primarily for sexual exploitation and for cheap labor purposes suggest the need to improve legal, socio-cultural, economic, political, ecological, environmental, and developmental methods along with focused attention to local community involvement and participation.